A hybrid dehumidifier model for real-time performance monitoring, control and optimization in liquid desiccant dehumidification system - Wang, Xinli (2013)
In this paper, a simplified, yet accurate hybrid model to predict the heat and mass transfer processes in a packed column liquid desiccant dehumidifier is developed. Starting from energy and mass balance principles, and by lumping the geometric parameters and fluids’ thermodynamic coefficients as constants, the derived model only requires two equations together with total seven parameters for predicting the heat and mass transfer status in the dehumidifier. Commissioning information together with Levenberg–Marquardt method can be used to identify these parameters. Compared with the existing liquid desiccant dehumidification system dehumidifier models, the proposed model is very simple, accurate and does not require iterative computations. Experimental results demonstrate their effectiveness in predicting heat and transfer performances over a wide operating range. The model is expected to be applied in operational optimization, performance assessment, fault detection and diagnosis in liquid desiccant dehumidification system.